Jihad Resolution and the Spirit of Struggle: Historical Traces of the Battle of November 10, 1945 - Syah, M Kautsar Thariq; Sa'adah, Putri Lailatus; Rofic, Zaenur; Hakim, Ajid; Anwar, Riyan Haqi Khoerul; Salsabila, Marisa Jahra; Syakira, Mutiara Khansa (UIN Sunan Gunung Djati Bandung, 2025)
The resolution of jihad on the November 10, 1945 incident became a major history of Indonesia after independence. However, this event is rarely depicted from the perspective of the role of religions in Indonesia, especially through religious fatwas during this battle. One of them is the fatwa of KH. Hasyim announcing, before the meeting attended by NU consuls throughout Java and Madura on October 22, 1945, all meetings of ulama agreed that the result of the deliberation was a decision regarding jihad as part of the struggle for independence. This article discusses the fatwas and appeals issued by several religions in Indonesia when the battle took place on November 10, 1945 in Surabaya. Research shows that there was a jihad fatwa to encourage resistance to the events of November 10, 1945. This was shown in the First People's Sovereignty Newspaper, an Islamic fatwa published through the People's Sovereignty Newspaper published on November 9, 1945, the contents of which were namely 60 Miljoen Kaoem Moelimin Indonesia Siap Melawan Fi Sabilillah, and dated November 24, 1945, the contents of which were in the Perjuangan Alim Oelama Menentoekan Hoekoem.